Transformational Educational Leadership: A Review of Relevant Literature with a Focus on Implications and Recommendations for Good Practice - Basaffar, Fatima (International Journal of Language and Literary Studies, 2022)
Educational leadership is a position that demands high-level skills and knowledge. The present paper attempts to summarize a few major aspects of transformational educational leadership. The paper first starts by briefly introducing the historical background of educational leadership in general and transformational leadership in particular. The paper then defines transformational leadership, focusing on the theory's main elements and its behavioural implications. Several relevant research is then introduced. The paper concludes by emphasizing the significance and effectiveness of the theory in the educational field. Finally, implications and recommendations for good practices are presented for further application.